The ESP32 Microcontroller as a Low-cost Teaching Tool for Mechatronics - Oberholster, Abrie (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
South African universities face unique challenges in teaching technology-intensive modules such as mechatronics. One such challenge is the variability in students' prior exposure to technology and programming. As such, not all students are equally confident in the technological skills required for the final year mechatronics and control module offered by the Department of Mechanical and Aeronautical Engineering at the University of Pretoria. However, recent technological advancements have opened up new possibilities. The ESP32-WROOM microcontroller, in particular, offers a versatile platform for learning mechatronics. Its compatibility with multiple programming languages ensures that students can choose the language they are most comfortable with to explore the world of mechatronics. The ESP32-WROOM's built-in wireless capabilities further make it ideal for Internet of Things (IoT) applications. This paper focuses on the selection of microcontrollers and their utilisation in the mechatronics course offered by the university.